The Dynamic Impact of Innovative Capability and Inter-firm Network on Firm Valuation: A Longitudinal Study of Biotechnology Start-ups - ZHENG, Yanfeng (Institutional Knowledge at Singapore Management University, 2010)
Prior research suggests that a high technology start-up's innovative capability and inter-firm network influence its performance and consequently, firm valuation. Few studies consider their joint influence and even fewer consider the temporal change of those effects on firm valuation. In this study, we propose that firm age, a key organizational variable, represents both the development of organizational routines from a start-up's perspective and the accumulation of accessible information from an investor's viewpoint. As such, an investor's evaluation of a high technology start-up's innovative capability and inter-firm network evolves with firm age. Using panel data of 170 biotechnology start-ups, our results suggest that the relative value of network status declines while the impact of innovative capability increases with firm age. Interestingly, there is a growing complementary effect of innovative capability and network heterogeneity on firm valuation. The implications of these findings for entrepreneurial practice and theories of firm capabilities and inter-firm network are discussed.